The View of Religious Figures on Mandiu Pasili Tradition in the Marriage of the Kaili Tribe from the 'Urf Perspective (Study in Wani Satu Village, Tanantovea District, Donggala Regency) - L.Irade, Alfa Singgani; Yasin, R. Cecep Lukman (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Mandiu pasili tradition is a wedding bathing tradition in the Kaili tribe. Thistradition to carry out two or three days after the marriage contract is implemented atthe bride's house door. The mandiu pasili tradition is still carried out by the Kaili tribein Wani Satu Village, which uses various tools and materials that contain philosophicalmeanings in its implementation. The purpose of the research is to describe howreligious leaders view the implementation of this tradition and how the position of themandiu pasili tradition is viewed from perspective ‘urf. The research method used isJuridical Empirical. The research approach used is descriptive and qualitative. Theresearch is located in Wani Satu Village, Tanantovea District, Donggala Regency. Datawere obtained through interviews and documentation. The results of the study are asfollows: first, religious leaders have two views on implementing the mandiu pasilitradition. Namely, the mandiu pasili tradition is classified as ‘urf sahih because thereare teachings of Islam in its implementation. On the other hand, the mandiu pasilitradition is classified as ‘urf fasid because it is considered not by Islam. Second, theposition of the mandiu pasili tradition in the perspective of ‘urf is classified as ‘urffasid because there are several implementations of this tradition that are not by theteachings of Islam. This tradition has good aims, and in terms of the tools and materialsused, none of them violate the teachings of Islam. However, with some processionsconsidered not by Islam's teachings, the whole mandiu pasili tradition is categorized as‘urf al-fasid.